Velopharyngeal dysfunction of neurogenic origin: Evaluating the use of gel implant injection augmentation - Khurram Khan; Michael Cadier (Wolters Kluwer Medknow Publications, 2017)
Objectives: Velopharyngeal dysfunction (VPD) secondary to neuromuscular pathology is well recognized. Surgical treatment in these patients using palatoplasty or conventional sphincteric and posterior flap-based pharyngoplasty is often contraindicated as they may further weaken or aggravate already impaired musculature. We report a small case series of patients who underwent successful long-term treatment for VPD of neurogenic origin using an injectable gel polymer to augment the posterior pharyngeal wall. Design: Three patients in whom a neuromuscular condition had led to the development of VPD underwent augmentation pharyngoplasty. Speech was compared pre- and post-operatively examining hypernasality, nasal emission, and nasalance scores and patient self-evaluation of outcome. Results: All three patients had improvement in parameters measured following pharyngeal injection augmentation. One patient noticed deterioration in speech intelligibility following initial injection into the velum: the implant polymer was easily removed and later reinjected in the posterior pharynx with good effect. Conclusions: The use of gel polymer injection pharyngoplasty in the treatment of neurogenic VPD was safe, simple, well tolerated, and easily reversible. However, due to recent severe complications reported from fat augmentation pharyngoplasty, we would not recommend its routine usage.